Pengaruh Good Corporateigovernance , Whistleblowing System Dan Pengendalian Internal Terhadap Pencegahan//Kecurangan (Fraud) Dalam Lembaga Perkreditan Desa - I Ketut Bagus Demi Ryana Putra; Ni Komang Sumadi; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2024)
This study aims to obtain empirical evidence on the Effect of Good CorporateGovernance , Whistleblowing System and Internal Control on Fraud Prevention invillage Credit Institutions in Mengwi Badung district. The Mengwi district LPD waschosen in this study because of the phenomenon of fraud that occurred in one of theMengwi District LPDs. The number of samples taken was 161 respondents. Datacollection techniques by observation, interviews, and questionnaires. Multiple linearregression analysis technique is the analysis technique used in this study. It was foundthat Good Corporate Governance had a positive and significant effect on the variable ofaccounting (fraud), Whistleblowing System had a positive and significant effect on thevariable of accounting (fraud) and Internal Control had a positive and significant effecton accounting (fraud) in the Village Credit Institution Mengwi district. This research cansupport the fraud triangle theory as a theoretical research implication. It is hoped thatthis research can provide input to improve Good Corporate Governance, WhistleblowingSystem, and Internal Control against fraud committed by LPD internal parties withpractical research implications.Keywords: Good Corporate Governance, Whistleblowing System, and Internal Controlof Fraud Prevention